Renaissance and renascences in Western art - Panofsky, Erwin (Paladin, 1970)
Panofsky's study brings welcome light into the darkness. His subject is the character of Renaissance art--in the strictest sense of the word-and its uniqueness in comparison with art produced during earlier revivals of the classical heritage.